Alteration of Conserved Alternative Splicing in AMELX Causes Enamel Defects. (October 2014) - Cho, E.S.; Kim, K.-J.; Lee, K.-E.; Lee, E.-J.; Yun, C.Y.; Lee, M.-J.; Shin, T.J.; Hyun, H.-K.; Kim, Y.-J.; Lee, S.-H.; Jung, H.-S.; Lee, Z.H.; et al.
Tooth enamel is the most highly mineralized tissue in vertebrates. Enamel crystal formation and elongation should be well controlled to achieve an exceptional hardness and a compact microstructure. Enamel matrix calcification occurs with several matrix proteins, such as amelogenin, enamelin, and ameloblastin. Among them, amelogenin is the most abundant enamel matrix protein, and multiple isoforms resulting from extensive but well-conserved alternative splicing and postsecretional processing have been identified. In this report, we recruited a family with a unique enamel defect and identified a silent mutation in exon 4 of the AMELX gene. We show that the mutation caused the inclusion of exon 4, which is almost always skipped, in the mRNA transcript. We further show, by generating and characterizing a transgenic animal model, that the alteration of the ratio and quantity of the developmentally conserved alternative splicing repertoire of AMELX caused defects in enamel matrix mineralization.